Improving the understanding and interpretation of myeloma screening among resident doctors and physician associates: a quality improvement project - Mahmoud Gouda; Hannah Hunter (Future Healthcare Journal)
Introduction: Myeloma is the second most common blood cancer in the UK, with a median age at diagnosis of 72.6 years.1 Patients with myeloma can initially present with vague and non-specific symptoms, making early diagnosis challenging. To improve early detection, a myeloma screen is commonly requested on medical wards. However, we observed a lack of clarity among resident doctors and physician associates regarding the specific tests included in the myeloma screen, as well as challenges in interpreting their results, which can lead to unnecessary specialist haematology referrals. Materials and methods: We conducted an online survey targeting resident doctors and physician associates to assess their knowledge of the myeloma screening process. The standard was the myeloma screen panel provided by The British Society of Haematology (BSH), which includes: full blood count (FBC), urea and creatinine, calcium, immunoglobulins, serum electrophoresis and serum free light chains.2Respondents were asked to select the appropriate tests for a myeloma screen from a list of commonly requested tests. Additionally, participants were asked to rate their confidence in interpreting myeloma screen results on a scale from 1 to 5. Results and discussion: A total of 34 responses to the survey were collected. Our results revealed significant variability in the participants' understanding of which tests should be requested for a myeloma screen (Fig 1). For instance, several tests were incorrectly included, such as C-reactive protein, chosen by 17 out of 34 (50%) respondees; 11 out of 34 (32.4%) selected a skeletal survey, and 11 out of 34 (32.4%) chose liver function tests.The BSH guidelines recommend serum free light chains rather than urinary Bence-Jones proteins to test for monoclonal light chains.2 Despite this, most respondents (94.1%) selected urinary Bence-Jones proteins as part of the myeloma panel.The results also revealed a lack of confidence among participants in interpreting myeloma screen results (Fig 2). Specifically, 16 out of 34 (47.1%) participants rated their confidence as 3/5, while 8 out of 34 (23.5%) rated their confidence as low, scoring 1/5. Conclusion: Our findings highlight a significant knowledge gap among resident doctors and physician associates regarding the appropriate tests to include in a myeloma screen. This lack of understanding can lead to unnecessary testing, increasing healthcare costs and potentially exposing patients to avoidable procedures. Additionally, insufficient confidence in interpreting test results often leads to unnecessary referrals to haematology specialists, wasting valuable resources and time. To address these issues, we implemented two targeted teaching sessions to raise awareness of the correct myeloma screening panel. We also collaborated with the laboratory to create an accurate order set within the hospital's electronic system for requesting myeloma screen blood tests. Finally, a local hospital protocol has been developed and will soon be published, providing clear guidance on how to request a myeloma screen and interpret its results accurately.